2021
DOI: 10.3390/livers1020006
|View full text |Cite
|
Sign up to set email alerts
|

Mac-2 Binding Protein Glycosylation Isomer for Screening High-Risk Esophageal Varices in Liver Cirrhotic Patient

Abstract: Background: Esophageal varices occur at middle to advanced stages of cirrhosis and are associated with increased mortality due to their potential for rupture and bleeding. The aim of this study is to examine the accuracy of a surrogate marker, Mac-2 binding protein glycosylation isomer (M2BPGi), for screening high-risk esophageal varices in cirrhotic patients. Methods: Ninety-four cirrhotic patients who underwent endoscopy screening at Cipto Mangunkusumo Hospital, Jakarta, Indonesia were included. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Several biochemical parameters in liver cirrhosis indicate hepatocyte damage or cholestasis, while others indicate stimulated synthesis of extracellular matrix proteins (laminin, hyaluronic acid, procollagen-III-peptide, Mac-2-binding protein glycosylation isomer) by stimulated HSCs (myofibroblasts), thus reflecting the degree of liver fibrosis. Various serum markers are suitable tools to detect clinically significant portal hypertension [ 119 , 120 , 121 , 122 , 123 ].…”
Section: Modulation Of the No-cgmp Pathway In A Healthy And Cirrhotic Livermentioning
confidence: 99%
“…Several biochemical parameters in liver cirrhosis indicate hepatocyte damage or cholestasis, while others indicate stimulated synthesis of extracellular matrix proteins (laminin, hyaluronic acid, procollagen-III-peptide, Mac-2-binding protein glycosylation isomer) by stimulated HSCs (myofibroblasts), thus reflecting the degree of liver fibrosis. Various serum markers are suitable tools to detect clinically significant portal hypertension [ 119 , 120 , 121 , 122 , 123 ].…”
Section: Modulation Of the No-cgmp Pathway In A Healthy And Cirrhotic Livermentioning
confidence: 99%
“…[26][27][28][29] Recent studies on M2BPGi in Indonesia focused on the accuracy of M2BPGi in chronic hepatitis C patients and screening of high-risk oesophagal varices in patients with liver cirrhosis, whereas in chronic hepatitis B patients, there were only evidence-based case reports. 28,30,31 This report concluded that M2BPGi could not be used as a diagnostic modality to detect liver fibrosis in chronic hepatitis B patients, because the sensitivity and specificity from these four studies showed that the M2BPGi are still insufficient to detect and rule out liver fibrosis in chronic hepatitis B patients. The difference in the cut-off value of M2BPGi to determine the stage of fibrosis in each study means that this value cannot be directly used as an accurate standard for determining advanced (F ≥ 3) liver fibrosis.…”
Section: Introductionmentioning
confidence: 98%
“…Previous study showed that among cirrhotic patients in Indonesia, M2BPGi measurement can be used to rule out high risk varices with negative predictive value > 90%. 4 Furthermore, considering the rising prevalence of metabolic associated-fatty liver disease (MAFLD) in Indonesia, it is also important to evaluate the diagnostic performance of M2BPGi level in CHB patients with MAFLD. Further studies on the role of M2BPGi and the factors that influence its performance will provide valuable insight into liver fibrosis and chronic liver diseases.…”
mentioning
confidence: 99%